THE POSSIBILITIES OF SURGICAL TREATMENT OF PATIENTS WITH RECCURENCES OF RECTAL CANCER - A. A. Hvatov; N. A. Maistrenko; A. A. Sazonov; Е. М. Sherstnova; V. V. Otochkin (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The objective of the study is to improve the results of treatment of patients with local recurrences of rectal cancer by implementing active surgical tactics within multidisciplinary approach.MATERIAL AND METHODS. The analysis of results of surgical treatment of 57 patients with the diagnosis: recurrence of a rectal cancer. The morphological structure of the primary tumor and its recurrences was adenocarcinoma of the intestinal type. In most cases, recurrences of rectal cancer were intraintestinal genesis with invasion of neighboring organs and structures. In addition, almost all patients had sufficiently paratumoral complications, significantly worsening their general condition.RESULTS. All recurrences and rerecurrences (repeated recurrences) of rectal cancer led to 73 operations: 9 patients underwent two interventions, 2 patients underwent three operations and 1 patients underwent four operations. The remaining 45 patients were operated on once. Resectability of recurrent tumors was 93 %. The development of complications in the postoperative period was noted in 37 % of patients. Hospital mortality was 1.5 %. The median duration of life reached 30.1 months. The overall three-year survival rate was 47.2 %.CONCLUSION. The following of the comprehensive diagnostic program and subsequent active surgical tactics allows achieving encouraging results of treatment in patients with recurrences of a rectal cancer.